Two-step synthesis of nano heterometallic catalysts for water treatment and biogasoline production / Mushtaq Ahmad - Mushtaq, Ahmad (2016)
Heterometallic catalysts are important in large-scale industrial production of green fuels, chemicals and industrial effluent treatment. The efficiency of a heterometallic catalyst is dependent on the molecular homogeneity, surface-morphological properties and metal compositions. These features are being enhanced with recent developments in nanotechnology. Currently, several chemical methods are available and more methods are being developed or modified to synthesize nano heterometallic catalysts. However, obtaining the required features remains a challenging task as the physical and chemical properties of nanoparticles differ significantly when used in bulk. To overcome this challenge, several researchers have developed nano-size heterometallic catalysts via Metal Organic Frameworks (MOFs) methods. In these methods, metals are attached to a suitable organic framework (ligand). However, these methods are not suitable for the synthesis of a wide range of heterometallic catalysts as each of these methods only produces a specific type of catalyst, which limits their use for industrial applications. Therefore, there is a need to develop a suitable method that can formulate a wide range of nano-size heterometallic catalysts for industrial processes. In this work, a two-step chemical process was developed and used to synthesize nano-size heterometallic catalysts. In the first step, precipitation method was effectively employed to produce monometallic and polymetallic complexes. 2,2'-bipyridine was used as the ligand to interlink metal atoms (Ni, Zn, Fe, Cu and Al). In the second stage, heterometallic complexes were thermally decomposed to produce nano oxide clusters. The crystalline products were characterized for particle size, structure, morphology, surface area and thermogravimetric property. The two-step process was found to greatly improve the size, morphology and yields of the crystalline materials. The yield of Ni, Zn and Al clusters were 81%, 80% and 78% respectively, while the yield of Ni-Zn, Zn-Al and Ni-Zn-Al complexes were 85%, 78.5% and 77% respectively. The two-step process was further utilized to produce supported type catalyst where Fe-ZSM-5, Fe-Zn-ZSM-5, and Fe-Zn-Cu-ZSM-5 heterogeneous catalysts were produced. Subsequently, the catalysts were used to treat wastewater containing organic recalcitrant contaminants (through Fenton oxidation process) and to produce biogasoline from palm oil. In the Fenton oxidation process, about 99% of color removal and 77% of total organic content (TOC) reduction were obtained. These values were significantly higher than the reported values in literature. When the same catalyst was used in the production of bio gasoline, the yield was about 56%, which was almost more than 8% compared to the literature values. The leaching analysis of the catalyst for the Fenton oxidation process revealed that only less than 2ppm of the metals were leached after a single use, which was in the permissible range as a heterometallic catalyst. Therefore, the present study proved that the newly developed two-step process was efficient and economical to produce heterometallic catalysts, which have a great potential for wastewater treatments and green energy applications due to higher degree of uniformity. In addition, availability of ligand (2,2'-bipyridine), solvents (ethanol, 2-proapnol and DMF) and their relevant information in the literature makes this 2-step process an attractive process for the production of a variety of heterometallic catalysts.